Asymmetric demand patterns for products with added nutritional benefits and products without nutritional benefits. Issue 9 (12th September 2016) - Yan, Ji; Tian, Kun; Heravi, Saeed; Morgan, Peter
Abstract : Purpose: This paper aims to investigate consumers' demand patterns for products with nutritional benefits and products with no nutritional benefits across processed healthy and unhealthy foods. This paper integrates price changes (i.e. increases and decreases) into a demand model and quantifies their relative impact on the quantity of food purchased. First, how demand patterns vary across processed healthy and unhealthy products is investigated; second, how demand patterns vary across nutrition-benefited (NB) products and non-nutrition-benefited (NNB) products is examined; and third, how consumers respond to price increases and decreases for NB across processed healthy and unhealthy foods is investigated. Design/methodology/approach: Here, a demand model quantifying scenarios for price changes in consumer food choice behaviour is proposed, and controlled for heterogeneity at household, store and brand levels. Findings: Consumers exhibit greater sensitivity to price decreases and less sensitivity to price increases across both processed healthy and unhealthy foods. Moreover, the research shows that consumers' demand sensitivity is greater for NNB products than for NB products, supporting our prediction that NB products have higher brand equity than NNB products. Furthermore, the research shows that consumers are more responsive to price decreases than price increases for processed healthy NB foods, but more responsive to price increases than price decreases for unhealthy NB foods. The findings suggest that consumers exhibit a desirable demand pattern for products with nutritional benefits. Originality/value: Although studies on the effects of nutritional benefits on demand have proliferated in recent years, researchers have only estimated their impact without considering the effect of price changes. This paper contributes by examining consumers' price sensitivity for NB products across processed healthy and unhealthy foods based on consumer scanner data, considering both directionalities of price changes.